Can climate-smart agriculture help to assure food security through short supply chains? A systematic bibliometric and bibliographic literature review - Mangirdas Morkūnas; Elzė Rudienė; Aleksander Ostenda (Business, Management and Economics Engineering, 2022)
Purpose – This paper aims to reveal potential research possibilities for enhancing climate-smart agriculture through short supply chains.